Biomarkers and immunomodulation as a treatment option for chronic pain conditions. (January 2011) - Gupta, Anita; Hewitt, Elizabeth; Oshinsky, Charlie
Inflammation is a well-established contributor to numerous medical conditions, and has discrete roles in disease processes ranging from coronary artery disease and end-stage renal disease to both acute and chronic pain conditions. In some disease processes, inflammatory biomarkers are used clinically to track disease progression and efficacy of treatment, as is seen with complex regional pain syndromes and coronary artery disease. The recognition of such inflammatory biomarkers, and the use of immunomodulating agents for the treatment of chronic pain conditions has become an area of interest, due in part to the successful use of immunomodulating therapy not only for disease progression, but also for symptomatic relief in patients with chronic inflammatory conditions. This article will review this topic and the evidence related to immunomodulation for chronic pain conditions.